2003
DOI: 10.1210/jc.2002-020380
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Study of Thyroid Function after Radiotherapy and Chemotherapy for a Childhood Brain Tumor

Abstract: The effect of craniospinal irradiation (CSI) vs. cranial irradiation (CIR) only with or without chemotherapy (CT) on the hypothalamus/pituitary (HP) thyroid axis was assessed in a population-based study of patients treated for a childhood brain tumor not directly involving the HP axis. Thyroid function was evaluated and compared with that in healthy controls (n = 27), measuring TSH, free T4, total T4, total T3, and TRH. The biological effective dose (BED) of radiotherapy, determined for the HP region and spine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 21 publications
6
55
0
5
Order By: Relevance
“…This cumulative incidence is much higher than that reported by Chow et al (15-year cumulative incidence of hypothyroidism: 1.6%), probably because their study also included patients treated with chemotherapy alone, and because the methodology used may have undervalued the incidence of hypothyroidism (retrospective study, self-reported thyroid dysfunction). 4 Primary hypothyroidism has been linked to exposure to thyroid radiation, 25 primarily in solid tumors such as Hodgkin lymphoma 15,16 and brain tumors, 10,14 although it was also found to be associated with cranial or craniospinal irradiation in patients with childhood acute leukemia. 4 Cranial irradiation in patients with acute lymphoblastic leukemia has long been suggested to play a role in hypothyroidism, 3,4,26 although a few authors have argued that the impact of prophylactic cranial radiation is controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cumulative incidence is much higher than that reported by Chow et al (15-year cumulative incidence of hypothyroidism: 1.6%), probably because their study also included patients treated with chemotherapy alone, and because the methodology used may have undervalued the incidence of hypothyroidism (retrospective study, self-reported thyroid dysfunction). 4 Primary hypothyroidism has been linked to exposure to thyroid radiation, 25 primarily in solid tumors such as Hodgkin lymphoma 15,16 and brain tumors, 10,14 although it was also found to be associated with cranial or craniospinal irradiation in patients with childhood acute leukemia. 4 Cranial irradiation in patients with acute lymphoblastic leukemia has long been suggested to play a role in hypothyroidism, 3,4,26 although a few authors have argued that the impact of prophylactic cranial radiation is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…1 It has long been known that the side effects which can occur include late thyroid complications, such as thyroid dysfunction [2][3][4][5][6][7][8][9] and thyroid cancer. [10][11][12][13] Thyroid dysfunction is rather frequent and has been mostly reported as a complication of irradiation, particularly for solid tumors, such as brain cancers 10,14 and Hodgkin lymphoma. 15,16 In leukemia survivors, thyroid complications have been mainly described as a consequence of central nervous system or total body irradiation and hematopoietic stem cell transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy also increases the risk of hypothyroidism. Central hypothyroidism is uncommon and usually occurs after cranial irradiation at doses higher than 30 Gy (26). By contrast, primary hypothyroidism is not rare in CCS who have been treated with external-beam RT involving the thyroid gland (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…This may truly reflect a dysfunction of the thyroid gland, especially as the coding of pituitary dysfunction of the thyroid axis according to the ICD-10 was allocated in the sub-chapter of other endocrine organs, but we cannot exclude misclassification at the time of discharge. An increased number of cases with primary hypothyroidism after radiotherapy and chemotherapy for a childhood brain tumor have been described in a cohort of Danish patients (19). The increased morbidity caused by diabetes was not surprising, it being well established that patients with GHD have reduced insulin sensitivity (20), and this may contribute to the increased circulatory mortality in women (13), as may untreated hypogonadism (21).…”
Section: Discussionmentioning
confidence: 99%